Addressing Vaccine Hesitancy Through a Comprehensive Resident Vaccine Curriculum - Zarina S. Norton; Kaitlyn B. Olson; Sandra M. Sanguino (Association of American Medical Colleges, 2022)
Introduction Vaccine hesitancy can lead to incomplete vaccination, increased risk of vaccine-preventable diseases, and distrust or conflict between physicians and patients. Yet many physicians are uncomfortable navigating vaccine hesitancy and educating vaccine-hesitant patients and families. We developed a vaccine hesitancy curriculum to increase vaccine knowledge, comfort, and communication skills in pediatric residents. Methods The curriculum consisted of four interactive 40-minute sessions delivered to pediatric residents over 10 months. The first two sessions discussed recommended childhood vaccines, the third session examined common vaccine misconceptions, and the final session reviewed vaccine hesitancy-specific communication skills, incorporating practice through role-playing. Residents completed pre- and posttests assessing knowledge and comfort as well as receiving a standardized patient (SP) assessment of vaccine-specific communication skills after the curriculum. Results Thirty-five residents were in the educational intervention group and 35 in a control group. Pretest scores did not differ significantly between the groups. The mean knowledge score for the intervention group increased from 47% on the pretest to 66% on the posttest. The mean self-reported comfort score (1 = low comfort, 5 = high comfort) for the intervention group increased from 2.9 on the pretest to 3.8 on the posttest. The control group showed no difference between pre- and posttest scores for knowledge or comfort. The mean postintervention SP assessment score was significantly higher for the intervention group (78%) than the control group (52%). Discussion Implementation of a comprehensive vaccine hesitancy curriculum resulted in improved vaccine knowledge, self-reported comfort, and communication skills among pediatric residents.